SUSTAINABILITY STATUS OF MANTIS SHRIMP (Harpiosquilla raphidea) RESOURCES IN THE WATERS OF LABUHANBATU, NORTH SUMATRA PROVINCE - Irham Huspa Khasahatan Siregar; Pera Herawati; Siti Zubaidah (Asian Journal of Aquatic Sciences, 2026)
This study was conducted from May to July 2026 in the Panai Hilir and Panai Tengah subdistricts of Labuhanbatu Regency. The objective of this study was to analyze the sustainability status of mantis shrimp (Harpiosquilla raphidea) resource management in the waters of Labuhanbatu, North Sumatra Province, using the . The research methods employed included secondary data analysis and a sample survey. The data were analyzed using Multi-Dimensional Scaling (MDS) through the RAPFISH (Rapid Assessment Technique for Fisheries) approach. Analysis of the sustainability status of mantis shrimp resource management using RAPFISH-Hamdangtis revealed that the average sustainability index value for mantis shrimp, based on five dimensions (environmental, mantis shrimp resource, facilities and technology, social and economic, and institutional and governance). The mantis shrimp resource in the waters of Labuhanbatu is considered unsustainable, with a value of 42.82 (<50). The environmental dimension showed the lowest score, indicating that habitat quality and ecosystem conditions are priority areas for management intervention. A plan to improve the sustainability of mantis shrimp management in the waters of Labuhanbatu, North Sumatra Province can leverage dimensions classified as relatively sustainable such as substrate deposition, hydro-oceanographic conditions, coastal degradation, until relevant regulations to address and improve less sustainable aspects